Unusual phenomenon in advanced hepatocellular carcinoma: declining alpha-fetoprotein levels despite disease progression - Haoran Shi; Xing Gao; Pan Liu; Lulu Xing; Zhixuan Qin; Yanfeng Pan (Discover Oncology)
Abstract In advanced hepatocellular carcinoma (HCC), some patients exhibit declining serum alpha-fetoprotein (AFP) levels despite disease progression. We investigated the characteristics, outcomes, and potential causes of this unusual phenomenon. We conducted a retrospective analysis of 139 patients with advanced HCC with baseline AFP ≥ 20 ng/mL, treated systemically and/or locally between March 2021 and May 2023. Patients were categorized into two groups: AFP abnormal trajectory group and AFP normal trajectory group. The ORR (0% vs. 18.8%, P = 0.037) and DCR (54.5% vs. 84.3%, P = 0.027) were significantly lower in the AFP abnormal group. The mPFS was 2.8 (95% CI: 1.34–4.25) months in the AFP abnormal group vs. 14.2 (95% CI: 10.57–17.82) months in the normal group (P < 0.001). The mOS was 14.0 (95% CI: 4.95–23.04) and 32.0 (95% CI: 16.4–47.5) months in the AFP abnormal and normal groups, respectively (P = 0.039). Combined targeted and immunotherapy (odds ratio [OR]: 15.35, 95% CI: 1.22–192.90, P = 0.034) and elevated neutrophil-to-lymphocyte ratio (OR: 1.29, 95% CI: 1.03–1.62, P = 0.025) were independent risk factors for abnormal AFP trajectories. A subset of patients with advanced HCC exhibit declining AFP levels despite disease progression, characterized by poor treatment response, accelerated progression, and poor prognosis.